(untitled) (Journal of Nepal Geological Society, 2015)
The Neogene fluival sediments (Siwalik Group) forming the southernmost hills in the Himalaya is well exposed along the Khutia Khola in the Far Western Nepal. The newly established lithostratigraphy is subdivided into the Jagati Formation (2110 m, equivalent to the Lower Siwalik) and the Kala Formation (2050 m, equivalent to the Middle Siwalik) in ascending order. Each formation is further divided into three members; the lower, middle and upper, based on the ratio of mudstone vs. sandstone beds as well as color and grain size of sandstone. The Jagati Formation is characterized by reddish-brown mudstones interbedded with very fine- to coarse-grained sandstones. Paleosols characterized with burrows, rhizoliths, desiccation cracks, concretions and nodules are present in higher proportion than thinly laminated or massive mudstone beds. The Kala Formation comprises thin- to thick-bedded, very fine- to very coarse-grained sandstones and pebbly sandstones interbedded with reddishbrown, greenish-grey to dark-grey mudstones. Sandstone beds exhibit "salt and pepper" appearance. In the lower part of the upper member sub-rounded to rounded pebbles are scattered along with trough and planar cross-laminations in sandstone beds, whereas the gravel size tends to be larger and few cobble size gravels also appear in the upper part. Thinly laminated or massive mudstones are common and paleosols are less frequent. The age of the boundary between the Jagati and Kala Formations (Lower-Middle Siwaliks) is around 11.05 Ma. The boundaries age between the middle and upper members of the Jagati Formation is around 12.7 Ma and between the lower and middle members of the Kala Formation is around 9.0 Ma. The dominance of finer sediments and thinner sandstone units than that of neighboring Siwalik successions indicate the fluvial fancies of the Khutia Khola section is deposited by a small river system and may represent the inter fluve setting of major river systems.